TRANSFORMASI LIMBAH MENJADI HARTA: REVOLUSI NATA DE PINA UNTUK KOMUNITAS PERTAKINA BLITAR - Lisanty, Nina; Pamujiati, Agustia Dwi; Azkiyah, Lailatul; Suryo Wibowo, Mochamad Agus; Putri Islami, Gadis Tiara; Kurniawan, Heru (Universitas Kadiri, 2024)
The objective of this study is to address the issue of pineapple skin waste produced by the PERTAKINA cooperative in Blitar, which primarily processes pineapple juice and other pineapple-based products, leaving large amounts of waste that currently have minimal use. Through collaboration with the PERTAKINA community, this study aims to create value from this waste by transforming it into nata de pina, a product with potential market appeal. This project involved training and mentoring sessions to equip participants with the skills and technology needed for waste processing, including production techniques, quality control, and basic management. Data were collected through observations, focus group discussions, and pre- and post-test evaluations, revealing significant knowledge gains among participants. This transformation of pineapple skin waste not only reduces environmental pollution but also provides new income-generating opportunities for the community, highlighting the potential of waste utilization in agricultural communities. The success of this initiative underscores the importance of technology transfer and continuous support to enable sustainable community-based waste management and product diversification.